(491) الاستخدامات العملية لجداول المدخلات والمخرجات Practical uses of input/output tables - فتحي الحسيني خليل (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة الصادرة عن معهد التخطيط القومي عام 1976 الأطر النظرية والتطبيقة لـ "تحليل المدخلات والمخرجات" (Input-Output Analysis)، حيث تستعرضه كأداة إحصائية ورياضية فائقة القوة لتصوير النشاط الإنتاجي وشبكة العلاقات المتشابكة بين مختلف قطاعات الاقتصاد القومي. ويركز البحث على قدرة هذه الجداول في الكشف عن "مواطن الاختناق" التي قد تعوق عملية التنمية، مبيناً أنها تتجاوز مجرد التوصيف الرقمي لتصبح وسيلة فعالة لاختبار مدى اتساق أهداف الإنتاج القومية مع الإمكانيات الفعلية للوحدات الإنتاجية، وضمان تحقيق توازن عام يربط بين الإنتاج واحتياجات الطلب النهائي (الاستهلاك والاستثمار والتصدير)، كما يُفصل الملف الاستخدامات العملية لهذا التحليل في رسم وتطوير السياسات الاقتصادية المثلى، بما في ذلك سياسات الاستثمار، والعمالة، والتجارة الخارجية، والضرائب، من خلال قياس الآثار المباشرة وغير المباشرة لأي تغير في أحد القطاعات على بقية أجزاء الاقتصاد. ويشرح البحث بالنماذج الرياضية والمصفوفات كيفية تحليل "البنيان الاقتصادي" والمفاضلة بين حالات التشابك (الكامل، والعشوائي، والمدرج)، مؤكداً على أن جداول المدخلات والمخرجات تمثل حلقة الوصل الضرورية بين التحليل الجزئي والتحليل الكلي، مما يساعد المخططين في التنبؤ بالتغيرات الهيكلية المستقبلية واتخاذ قرارات تنموية رشيدة تتناسب مع واقع الإمكانيات الوطنية This 1976 memorandum from the National Planning Institute examines the theoretical and applied frameworks of Input-Output Analysis (IIA), presenting it as a powerful statistical and mathematical tool for mapping productive activity and the interconnected relationships between various sectors of the national economy. The research focuses on the ability of these tables to identify bottlenecks that may hinder the development process, demonstrating that they transcend mere numerical description to become an effective means of testing the alignment of national production targets with the actual capabilities of production units. This ensures a general balance between production and the needs of final demand (consumption, investment, and exports). The memorandum also details the practical applications of this analysis in formulating and developing optimal economic policies, including those related to investment, employment, foreign trade, and taxation, by measuring the direct and indirect effects of any change in one sector on the rest of the economy. The research uses mathematical models and matrices to explain how to analyze the "economic structure" and differentiate between entanglement states (complete, random, and graduated), emphasizing that input-output tables represent the necessary link between micro and macro analysis, thus helping planners predict future structural changes and make sound development decisions that align with the reality of national capabilities.